Utility and the "Ordinalist Fallacy" - Armstrong, W. E. (Review of Economic Studies, 1958)
Journal Article Utility and the “Ordinalist Fallacy” Get access W. E. Armstrong W. E. Armstrong Southampton Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 25, Issue 3, June 1958, Pages 172–181, https://doi.org/10.2307/2295985 Published: 01 June 1958